Identification of pathogenic Aspergillus isolates from captive birds in Australia. (8th December 2017) - Talbot, Jessica J; Thompson, Paul; Vogelnest, Larry; Barrs, Vanessa R
Abstract: Aspergillosis is a major cause of severe respiratory disease in birds. The prevalence of cryptic section Fumigati and other non– Aspergillus fumigatus species as causative agents is unknown. Species identity was determined in 30 isolates from affected birds from zoos, pet birds and poultry by PCR of the ITS1-5.8S-ITS2 and partial β-tubulin genes. The most prevalent isolate was A. fumigatus sens. str. in 87% (26) cases. Other Aspergillus species were identified in 13% (4) cases, including A. restrictus (1), A. flavus sens. str. (2), and A. nidulans- clade (1). This is the first report of A. restrictus causing avian disease.